2021
DOI: 10.1073/pnas.2022311118
|View full text |Cite
|
Sign up to set email alerts
|

Selective depletion of a CD64-expressing phagocyte subset mediates protection against toxic kidney injury and failure

Abstract: Dendritic cells (DC), macrophages, and monocytes, collectively known as mononuclear phagocytes (MPs), critically control tissue homeostasis and immune defense. However, there is a paucity of models allowing to selectively manipulate subsets of these cells in specific tissues. The steady-state adult kidney contains four MP subsets with Clec9a-expression history that include the main conventional DC1 (cDC1) and cDC2 subtypes as well as two subsets marked by CD64 but varying levels of F4/80. How each of these MP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Such a definition has limitations and may not be tenable in the dynamics of acute disorders with changing microenvironments when cell types exhibit phenotypic plasticity, and lineage tracing-related definitions are less valuable. However, it has become clear that MP subtypes have specific functions in pathology (22,23). Defining cell types by lineagespecific transcription factors is a powerful tool to establish the functions of MP in immunity.…”
Section: Development and Definition Of Mononuclear Phagocytesmentioning
confidence: 99%
“…Such a definition has limitations and may not be tenable in the dynamics of acute disorders with changing microenvironments when cell types exhibit phenotypic plasticity, and lineage tracing-related definitions are less valuable. However, it has become clear that MP subtypes have specific functions in pathology (22,23). Defining cell types by lineagespecific transcription factors is a powerful tool to establish the functions of MP in immunity.…”
Section: Development and Definition Of Mononuclear Phagocytesmentioning
confidence: 99%
“…Among kidney myeloid cells, macrophages and dendritic cells play important roles during both the initial injury and subsequent healing process. Unlike in other tissue microenvironments where CD11c (gene name Itgax ) is used to specifically identify dendritic cells, most non-neutrophil myeloid cells, including macrophages and some monocytes, express CD11c + ( Kawakami et al, 2013 ; Lever et al, 2019 ; Salei et al, 2020 ; Zimmerman et al, 2020 ; Salei et al, 2021 ; Privratsky et al, 2023 ). The roles of CD11c-expressing myeloid cells during AKI are complex and context-specific as CD11c + myeloid cells promote cyst formation in a cystic disease model ( Zimmerman et al, 2019 ); whereas deletion of CD11c + cells aggravates cisplatin- and sepsis-induced AKI ( Tadagavadi and Reeves, 2010 ; Privratsky et al, 2023 ), and impairs the healing process and promotes pro-inflammatory cytokine generation following ischemic AKI ( Kim et al, 2010 ; Lu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently revisited the role of MPs in cisplatin‐induced kidney injury using cell type‐specific depletion models. We found that the intrinsic potency reported for CD11c + cells to limit cisplatin toxicity is specifically attributed to CD64 + DC, while cDC1 and cDC2 are dispensable [120]. In nephrotoxic nephritis on the other hand, it has been shown that cDC1 protect the tissue, while cDC2 seem to play a pro‐inflammatory role [121, 122].…”
Section: Introductionmentioning
confidence: 99%